Sustainable development goals : the impact of sustainability measures on wellbeing - Sharma, Ridhima; Bhardwaj, Indira; Grima, Simon; Sachdeva, Timcy; Sood, Kiran; Özen, Ercan (Contemporary studies in economic and financial analysis ;, 2024)
The global community is at a critical moment in its pursuit of the Sustainable Development Goals (SDGs); crises are threatening decades of development gains, further delaying the urgent transition to greener, more inclusive economies, and throwing progress on the SDGs even further off track. When it comes to sustainability and combating our current climate emergency, we need sustainable solutions that can protect our water, energy and food resources while also aiming for zero waste. Sustainable Development Goals considers these solutions throughout twelve chapters, introducing the subject of sustainable development then delving into detail of the framework to address these gaps and shortages in different disciplines and sectors. The global drivers of change are analysed and the opportunities and challenges of attainment of development goals are investigated. Contemporary Studies in Economic and Financial Analysis publishes a series of current and relevant themed volumes within the fields of economics and finance. Both disciplinary and interdisciplinary studies are welcome.